Familial adenomatous polyposis, diagnosis and surveillance strategies: review article - Sima Sedighi (Tehran University Medical Journal, 2020)
Familial adenomatous polyposis is characterized by over 100 colorectal adenomas in the colorectum. The disease equally affects both sexes, with an incidence estimated at 1.14025-1.8300. The disease is premature in people with familial adenomatous polyposis. Patients suffering from familial adenomatous polyposis have a range of extra-intestinal diseases such as papillae, gastric, small intestine, and duodenal polyps; cutaneous wounds (lipomas, fibromas, and epidermoid cysts); desmoid tumors; osteomas; nephroderma retinal pigment epithelium, including hepatoblastoma and thyroid cancers; and pancreas, biliary system, and brain cancer. Familial adenomatous polyposis is characterized by >100 polyps in the colon that are often observed on the left side of the colon and rectum. A germline mutation in the adenomatous polyposis coli gene that can be clinically and genetically diagnosed is responsible for this disease. Several methods are available for testing the adenomatous polyposis gene. Whole-gene sequencing of all adenomatous polyposis coli exons and exon-intron boundaries with maximum sensitivity for determining adenomatous polyposis coli mutations is not affordable. Another method, the protein shortening assay, correctly identifies 80% of the mutations in families who show familial adenomatous polyposis and is less expensive than complete gene sequencing. The application of a COX-2 inhibitor for chemical prevention is limited in patients showing familial adenomatous polyposis because of cardiovascular toxicity. Aspirin does not negatively impact cardiovascular diseases and is even used as primary pharmacotherapy in patients who demonstrate cardiovascular risk factors.   After 55.7 months of the diagnosis in hereditary CRC carriers, the incidence of cancer can be decreased by a dose of 600 mg/day aspirin for 25 months. After diagnosis, patients should undergo prophylactic proctocolectomy or ileoanal pouch. Undiagnosed patients having a family history of FAP must be referred to a genetic counselor and enrolled in optimal genetic and clinical surveillance programs. Recent advancements in endoscopic technology, e.g. high-resolution endoscopy, double-balloon endoscopy, and capsule endoscopy have enabled the comprehensive study of the gastrointestinal tract. Despite the limited evidence, more studies on these novel endoscopic technologies may modify the surveillance strategies for FAP patients.